An Autonomic Service Discovery Mechanism to Support Pervasive Device Accessing Semantic Grid. - Guan, T; Zaluska, E; Roure, D (IEEE, 2007)
An important challenge of integrating pervasive devices into Grid environment to enhance pervasive device capabilities is that pervasive devices need to locate, find, select and invoke the appropriate Grid services in an autonomic and flexible way. However, at this stage, both Grid service description and discovery standards are not very sophisticated. Semantic web technology benefits the concept of Grid services on pervasive devices by adding machineprocessable explicit knowledge into the interaction between pervasive devices and Grid services. In this paper, we have presented a semantic-based Grid service discovery mechanism to support pervasive device accessing Grid services. In order to protect personal privacy in the pervasive computing environment, a service discovery restricting mechanism is also built to ensure the service can automatically be hidden for unauthorized users. © 2007 IEEE.